2021
DOI: 10.1186/s13578-021-00650-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal delivery of therapeutic modulators through the blood–brain barrier; promise and pitfalls

Abstract: Nowadays, a large population around the world, especially the elderly, suffers from neurological inflammatory and degenerative disorders/diseases. Current drug delivery strategies are facing different challenges because of the presence of the BBB, which limits the transport of various substances and cells to brain parenchyma. Additionally, the low rate of successful cell transplantation to the brain injury sites leads to efforts to find alternative therapies. Stem cell byproducts such as exosomes are touted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 229 publications
(300 reference statements)
1
81
0
Order By: Relevance
“…The lack of success in brain drug delivery with stem cells has led to the development of exosomes as a brain drug delivery vehicle [295,296]. Exosomes are naturally occurring extracellular vesicles, which are released from the plasma membrane of cells, and may be taken up by neighboring cells.…”
Section: Exosomes For Brain Drug Deliverymentioning
confidence: 99%
“…The lack of success in brain drug delivery with stem cells has led to the development of exosomes as a brain drug delivery vehicle [295,296]. Exosomes are naturally occurring extracellular vesicles, which are released from the plasma membrane of cells, and may be taken up by neighboring cells.…”
Section: Exosomes For Brain Drug Deliverymentioning
confidence: 99%
“…Beyond these mechanisms, some reports demonstrate the existence of the ESCRT-independent pathway in the biogenesis of MVBs, which were confirmed after the suppression of four main subunits of the ESCRT complex ( Juan and Fürthauer, 2018 ). In support of this notion, it has been shown that the release of Exo in mouse oligodendrocytes is an ESCRT-free mechanism via the activity of ceramide-generating enzyme neutral sphingomyelinases (nSMase) ( Heidarzadeh et al, 2021 ). Tetraspanins, as intracellular effectors, partake in the biogenesis of Exo and cargo sorting ( Chairoungdua et al, 2010 ).…”
Section: Exo Biogenesismentioning
confidence: 96%
“…These features show that Exo are the key regulators during physiological and pathological conditions with specific factors that give us valuable data about the status and intensity of pathologies. Because Exo can easily distribute in the systemic circulation, studying exosomal profiles in blood samples is helpful in the determination of pain-related factors ( Heidarzadeh et al, 2021 ). Despite the existence of a blood–brain barrier with selective permeability, Exo can engage several strategies to cross this natural barrier from the brain to the blood side and vice versa ( van Dijk et al, 2010 ).…”
Section: Exo Biogenesismentioning
confidence: 99%
“…Overall, EVs possess ability to actively penetrate biological barriers. Although the underlying mechanism remains unclear (Heidarzadeh et al, 2021) and how to control the penetration of EVs in biological barriers remains a mystery, EVs are promising to be used as drug delivery vehicles for central nervous system diseases. Noteworthy, abnormal cell-derived EVs should be removed to avoid cancer risk.…”
Section: Evs Actively Cross Biological Barriersmentioning
confidence: 99%